Islamic legal perspectives on genetically modified food - Bouzenita, Anke Sandra (The International Institute of Islamic Thought, 2010)
Genetically modified food (GMF) is part of our realities as consumers worldwide. The techniques and possibilities involved do require an Islamic legal (fiqh) study as to assess GMF with regard to its consumption, production and related research. The paper focuses on placing the study of GMF within a holistic context, under consideration of the societal background and rationale it has been developed under. It investigates into the possibility of transferring fiqh devices such as istihalah (chemical transformation), istihlak (extreme dilution) and others to GMF combining genetic material from permissible and non-permissible sources. It raises a number of deliberations and concerns with regard to the usage of the ‘maqasidic’ scheme and discusses the permissibility of GMF under the aspects of changing creation or harnessing nature.